Możliwości podejmowania działań integracyjnych wśród producentów rolnych w świetle obowiązujących w Polsce regulacji prawnych - Lemanowicz, Marzena (Possibilities of Undertaking of Integration Activities among Farmers Based on Present Polish Regulations, 2006)
In the article there are presented reasons which cause necessity of undertaking of integration activities among farmers. An essential part of the work is to describe present regulations and rules of farmers' organisation in a group activity. There are presented conditions under which farmers can form producers groups and producers' organisations. Creation of such entities is very important because of improvement in competitiveness of Polish agriculture. Moreover, only these organisations which fulfil requirements included in acts can apply for public support.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 21-27